COVID-19 in the UK- Experience from The Frontline - Aryal, Kamal (Journal of Lumbini Medical College, 2020)
Start of the pandemic At the end of February, I was undertaking a mini fellowship on Trans-anal Total Meso-rectal Excision (TaTME) in Switzerland. The number of cases infected with corona virus disease (COVID-19) and deaths were rising exponentially in Italy. As the virus hit the UK, I was still able to complete ‘Non-Technical Skills for Surgeons (NOTSS) for trainees’ course at the deanery office at Fulbourn, Cambridge on the 13th of March 2020.